STUDY OF NEUROVIRULENT PROPERTIES OF VACCINE AGAINST CULTURAL LIVE RUBELLA - A.N. Mironov; A.A. Tsaan; D.S. Bushmenkov; A.A. Romanova; V.A. Merkulov; N.N. Stepanov (Union of pediatricians of Russia, 2010)
Experts at FSUE R&D Centre Microgen of the RF's Healthcare Ministry have developed a national drug designed to prevent rubella - Cultural live vaccine against rubella on the basis of vaccinal strain RA 27/3. A pre-clinical study was conducted to examine neurovirulent properties of the seed virus (S. V. 30 passage) and production strain RA 27/3 of rubella virus (P. S. - 30 passage) on rubella virusantibody negative cynomolgus monkeys. The study was conducted at the laboratory of the Branch of Federal State Institution «48 Central Research Institute of Russia's Defense Ministry - Virologic Centre» pursuant to requirements of 43 of the report issued by WHO Expert Committee on biological standardization. During the experiment, the following indicators were examined: neurovirulency of the production strain; neurovirulency of the seed virus; immunogenic properties of the seed virus and production strain; contagiousness of the seed virus and production strain. Results obtained in the study indicate that the seed virus and production strain have no neurovirulent properties and contagiousness, and that the developed vaccine has high immunogenic properties. Key words: vaccine against rubella, seed virus, production strain, neurovirulency, contagiousness, immunogenicity. (Pediatric Pharmacology. - 2010; 7(4):125-128)